2014
DOI: 10.1113/expphysiol.2013.072868
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myometrial transcriptome changes associated with spontaneous human labour by high‐throughput RNA‐seq

Abstract: New Findings r What is the central question of this study?In this study, we sought to survey the total transcript repertoire of human myometrium, comparing samples taken from patients at term who were not in labour with samples taken at term in spontaneous labour. These sequenced transcriptomes show the repertoire of possible proteins and their variants in myometrial smooth muscle, as well as transcriptional changes associated with term spontaneous labour. r What is the main finding and its importance?We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 42 publications
10
120
2
Order By: Relevance
“…These authors showed that Cx43 expression remains unchanged between the two sample groups, whereas Cx45 expression is significantly downregulated in the 'in labour' group in comparison with the 'not-in-labour' group (electronic supplementary material, figure S12). These results are in accordance with our data, which furthermore suggest that the significant changes found by Chan et al [35] were owing to changes in expression taking place in the inner myometrium as opposed to the outer myometrium. Our model simulations show that an elevated proportion of Cx43 proteins is a key factor in modulating conductance.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These authors showed that Cx43 expression remains unchanged between the two sample groups, whereas Cx45 expression is significantly downregulated in the 'in labour' group in comparison with the 'not-in-labour' group (electronic supplementary material, figure S12). These results are in accordance with our data, which furthermore suggest that the significant changes found by Chan et al [35] were owing to changes in expression taking place in the inner myometrium as opposed to the outer myometrium. Our model simulations show that an elevated proportion of Cx43 proteins is a key factor in modulating conductance.…”
Section: Discussionsupporting
confidence: 94%
“…Our experimental data indicate downregulation of Cx45 expression in the rat as labour approaches, in contrast to Cx43 expression where no change at the end of pregnancy appears to be evident. Chan et al [35] found similar results in human myometrium, analysing the RNA of myometrial samples from pregnant women (five from women in labour, and five from women at full term, but not in labour). These authors showed that Cx43 expression remains unchanged between the two sample groups, whereas Cx45 expression is significantly downregulated in the 'in labour' group in comparison with the 'not-in-labour' group (electronic supplementary material, figure S12).…”
Section: Discussionmentioning
confidence: 61%
“…First, myosin light chain kinase and myosin light chain phosphatase are inhibited by phosphorylation and dephosphorylation, respectively (8 ] i to basal levels (9). The predominant K + channel in the myometrium is the largeconductance, voltage-gated, Ca 2+ -activated K + channel (BK Ca ), also known as MaxiK/hSlo/KCa1.1 (10)(11)(12). Opening of the BK Ca channel provides a strong repolarizing current to maintain MSMCs at a polarized membrane potential, thus preventing voltage-gated Ca 2+ influx and contraction.…”
Section: +mentioning
confidence: 99%
“…This transition is controlled, in part, by a complex regulation of ion channel activity. Multiple types of ion channels are responsible for changes in the membrane potential in MSMCs (Sanborn, 2000; Shmygol et al, 2007a; Chan et al, 2014); potassium channels, in particular, play an important role in controlling membrane potential and attenuating excitation to maintain quiescence in pre-labor MSMCs.…”
Section: Bkca Channel Function In Myometriummentioning
confidence: 99%